Impacto de la dirección estratégica en la gestión comercial del colorante índigo - Carbajal Gutiérrez, Félix Marco Antonio (2025)
This article analyzed the influence of strategic direction on the commercial management of indigo as the main chemical input in the textile manufacturing process for denim production between 2018 and 2019. The study identified three highly effective generic strategies to achieve better performance than the competitors in this industry sector: commercial leadership, differentiation, and business focus. The study concluded that applying strategic direction in the commercial management of indigo dye improves the company’s competitive position in the local market, enabling it to secure large-scale commercial agreements with major manufacturing companies that use this dye in the Peruvian textile sector. Ultimately, it is demonstrated that implementing strategic direction in the commercial management of indigo dye increases the sales of this input, thereby improving the company’s annual turnover.